An Effective Method for Electromagnetic Parameter Measurement of Flexible Materials Based on Air Coaxial Line - Jinjing Ren; Mingjie Sheng; Zhongyuan Zhou (International Journal of Antennas and Propagation)
When measuring the electromagnetic parameters of flexible material with an air coaxial line, the specimen is prone to bend and deform in the fixture, which results in erroneous results. In order to solve this problem, this paper proposes a new measurement method. Firstly, a rigid material is selected and loaded into the air coaxial line for two-port S parameters measurement. Then, the flexible material is attached to one end of the rigid material and loaded into the air coaxial line together for repeated two-port S parameter measurement. According to the S parameters measured and the two-port network cascading theory, the S parameters of the flexible material separately loaded in the fixture can be deduced. Finally, the electromagnetic parameters of the flexible material can be calculated by the Nicolson−Ross−Weir (NRW) method. Experimental results show that the method proposed is effective and reliable.